The Relationship between Gender Equality in the Qur’an and Sunnah and the Sustainable Development Goals 2030 - “Presentation and Evaluation” (The International Journal of Educational Sciences and Arts, 2024)
This research deals with the relationship between the concept of gender equality in the Qur’an and Sunnah, and what is stated in the 2030 Sustainable Development Goals document issued by the United Nations, and addressing the problems of racial discrimination between the sexes that peoples suffer from in all previous and contemporary civilizations, and clarifying this concept by stating the legal basis for its objectives and the wisdom of it in the Qur’an and Sunnah.The research included two topics: defining the concept of gender equality in the Qur’an and Sunnah and in the Sustainable Development Goals document and the difference between them. The second: areas of the relationship between gender equality in the Qur’an and Sunnah and the Sustainable Development Goals document.In this research, I adopted the inductive-deductive approach in analyzing legal texts and what is stated in international agreements.The research concluded with important results, which are:-      Explaining the greatness of the Islamic religion, including its provisions that are appropriate for all times and places, with regard to gender equality.-      Supporting the United Nations initiatives to enable gender equality within the sustainable development goals, in a manner that does not contradict what is stated in the Qur’an and Sunnah.
Keywords: Equality; Gender; Discrimination; Justice; Sustainable Development